Evolution of the landscape and pedodiversity on volcanic deposits in the south of the Basin of Mexico and its relationship with agricultural activities - Solleiro-Rebolledo, Elizabeth; Rivera-Uria, Yazmín; Chávez-Vergara, Bruno; Diaz-Ortega, Jaime; Sedov, Sergey; Alcalá-Martínez, Jorge René; Beltrán-Paz, Ofelia Ivette; Jardines-Martínez, Luis Gerardo (REVISTA TERRA LATINOAMERICANA, 2019)
In this work, we present the results of a soil study in the Teuhtli volcano, located to the south of the Basin of Mexico with the aim to understand the pedogenetic pathways and the evolution of the landscape dynamics. Two different types of soil prof iles were sampled: in “conserved” areas, with less anthropogenic influence and in sites with intense agriculture activities since pre-Hispanic times. The three conserved prof iles are located in different landscape positions: the Cima prof ile in the summit, the Ladera prof ile in the high slope, and the Yotecón in a lower position of the piedemont. The agriculture prof iles are La Cruz, La Era and El Llano, situated in the foothill. Properties in both kind of soils are similar, however, in agriculture sites, structure (evaluated in macro and microscale) is weaker, total organic carbon content is smaller and bulk density is higher. Both soils show two main pedogenetic processes: andosolization and carbonate formation. Despite the age of the parent material (36 000 years), the Andosol phase has not been lost. This is because of the geomorphological dynamics of the zone, in which the processes of erosion and colluviation promote soil loss, restarting the pedogenetic clock. The detection of lithological discontinuities (by the Ti/Zr ratio) documents these processes. By the other hand, the formation of pedogenic carbonates is governed by the seasonal conditions of drought. The age of these carbonates places their formation in the mid-Holocene, an epoch for which drier conditions are detected in other sites of the Basin of Mexico. The agricultural land use has also promoted morphological, chemical and physical changes in the soils. The continuous tillage of the sites has prevented the soils from developing. This could have a negative effect on the fertility of those soils currently used to sustain the peri-urban agroecosystems of Mexico City.